Different concentrations of Ti4+ as a donor and electronic properties of Bi2-xTixO3 - Alshoaibi, Adil; Hussain, Fayaz; Mohsin, Fatima; Alnaim, Nisrin; Almulhem, Najla (Frontiers in Materials, 2023)
Bi(2-x)TixO3 (x= 0, 0.01, 0.03. & 0.05) (BO-xT) ceramics are prepared by conventional solid-state route followed by low sintering temperatures. X-ray diffraction analyses show the presence of the monoclinic phase of Bi2O3. The electrical conductivities at room temperature concerning the frequency (ranging from 25 kHz to 5MHz) and Seebeck Coefficient ranging from 50 °C to 400 °C were measured. With an increase of Ti (dopant) content, the conductivity and Seebeck Coefficient increased with respect to the temperature increment. The BO-3T has the highest Seebeck value (47µV/°C), which shows a higher carrier concentration. In terms of electrical conductivities, the BO-5T ceramic shows the maximum electrical conductivity i.e. 2.0x10-9 µS/m as compared to other samples, which exhibit the presence of free electrons. Moreover, relative permittivity (dielectric constant) and dielectric loss are also measured concerning the frequency at room temperature to investigate the dielectric behavior of the ceramics. This low-temperature sintering ceramics will open new applications in the domain of electronic materials.